Advancements in nanoparticle applications for targeted drug delivery: benefits and implications - T, Srinivas.; D, Parvathi.; Devi U, Anitha; M, Venkateshwarlu; T, Ugandhar (International Journal of Biological Research, 2024)
Nanoparticles have emerged as a new technique in the field of targeted drug delivery, providing major benefits in terms of therapeutic results. The present study studies the improvements in nanoparticle applications for targeted medication administration, focusing on their advantages and wider implications. Nanoparticles, because to their nanoscale size, distinct physicochemical features, and capacity to be functionalized with diverse ligands, can easily penetrate biological barriers and transport medications directly to sick cells, reducing off-target effects and increasing treatment effectiveness. Nanoparticles’ adaptability allows them to encapsulate a wide range of therapeutic substances, such as tiny molecules, proteins, and nucleic acids, expanding the range of treatable disorders. Recent advances have focused on optimizing nanoparticle surface properties and composition to increase biocompatibility, circulation time, and targeted delivery capabilities. Polymeric, lipid-based, and inorganic nanoparticles have made significant advances in drug loading capacity, controlled release profiles, and selective cell targeting. Furthermore, stimuli-responsive nanoparticles that release medications in response to biological signals or environmental changes are shown encouraging outcomes in preclinical and clinical trials. These breakthroughs have far-reaching ramifications, possibly altering the therapeutic landscape for a variety of illnesses, including cancer, cardiovascular disease, and neurological disorders. However, scalability, repeatability, and long-term safety remain crucial topics of ongoing study. The combination of nanotechnology with personalized medical techniques has the potential to produce extremely effective, patient-specific medicines. To summarise, the continuous development of nanoparticle-based drug delivery systems offers a significant step towards more accurate, efficient, and safe treatments. This research focuses on nanoparticles’ unique contributions to targeted medication delivery, as well as potential future paths and consequences for medical science and patient care.